(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
In modern linguistics, the text is characterized as the central communicative unit. Since the title is one of the most important elements of any text structure, you must first deal with the definition of the text itself, which is an element of the whole about the title. The phenomenon of integral textual familiarity is an important research phase that enables a qualitative examination of the topic of integrity.